A study of the effect oil extract of Trigonella foenum-graecum and Peganum harmala seeds on the life of Tribolium castaneum - Warqaa Latef Salman (The Bioscan, 2024)
This study was conducted to investigate the effect of different concentrations of Trigonella foenum-graecum and peganum harmala seeds oil on the life of Tribolium castaneum. The results showed: With a concentration of 8% after 48 hours of treatment, T. foenum-graecum and Peganum harmala seed oil had the highest mortality rate for the fourth instar larvae, reaching 96.7%, and 73.7% respectively, the lowest mortality rate for the first larval instar, 26.7% and 16.7% respectively at a concentration of 2% after 24 hours of treatment, the highest mortality rate for adults was 96.7% and 87.7% respectively at a concentration of 8% after 72 hours of treatment, and the lowest mortality rate was 16.7% and 10.7% respectively after 24 hours at a concentration of 2%.